Influence of Age and Sex on Muscle Fiber Type and Myoglobin Content in different Strains of Japanese Quail - M, Shashi Kumar; Prakash, Gnana; K., M. Sudhakar Reddy; G., Purshotham Rao (Journal of Meat Science, 2012)
Three commercial meat type strains of Japanese quails (white, black and spotted brown) were slaughtered at 5, 6, 7 and 8 weeks of age and meat samples were collected from breast muscles. Male birds recorded significantly higher myoglobin (0.92 vs 0.79 mg/gm) and per cent red muscle fiber (84.79 vs 83.82) than females. The overall myoglobin content, in the meat of Japanese quails belonging to white, black and brown strains was 0.87, 0.86 and 0.84 mg/gm, respectively while the respective overall per cent red muscle fiber content was 83.41, 84.86 and 84.64. From the present study it is found that the quail meat is predominantly made of red muscle fibers and is hence suitable for processing and consumption similar to other red meats.
Keywords: Japanese quails; myoglobin; red muscle fibre